PENDEKATAN PEMBELAJARAN IPS BERBASIS MUSEUM - Muhammad Nur (CV. ADIBA AISHA AMIRA, 2022)
The results of this study indicate that; 1) A visit to the Museum is something worthy of attention as a source of visual learning for students. Observation and analysis in deepening historical social studies material is a requirement for students in studying history, because children are required not only to have cognitive competence, but also affective and psychomotor. Through direct museum visits, it is hoped that it can change students' perceptions that social studies lessons are interesting and fun. The use of the museum has a positive impact on social studies learning, especially history, namely learning outside the classroom with a different atmosphere while at the same time increasing students' critical abilities. 2) Adjustment of competency standards and basic competencies for social studies subjects indirectly makes teachers also a source of learning that can increase student learning motivation. In addition, the learning objectives that have been planned will be strived to be achieved optimally so that the museum-based learning approach in social studies history is more effective. The realization of Project base learning assignments resulting from visits to museums becomes a student experience that is not only limited to visits but continues with discussions in class. 3) Utilization of Museums Museums are representative historical social studies learning resources to add insight and knowledge about past events so that students have love for their nation and homeland. Museum collections that are utilized in social studies history lessons for MTsN 2 Tanah Laut students have taught students to understand past events, learn to analyze and think critically. However, the use of museums must still be in accordance with basic competencies and learning objectives. The stages that must be carried out by students so that the implementation is optimal, namely: developing questions according to the theme given by the teacher to museum staff, data collection, data analysis and data synthesis. Students appreciate the museum visit by writing articles or scientific works about museums.